A review on the role of postpartum homecare program in identification, managing and preventing common complications - Dahab, Amaal Abdo; Miski, Samer Sameer; Hajjaj, Asia Mohamed; Alnughmush, Munthir Saad; Buradhah, Fatemah Eid; Basakran, Ghadeer Ghalib; Bahshwan, Amjad Abdulqader; Aseeri, Khalid Ibrahim; Alshahrani, Ahlam Rashed; Almoagal, Hayam Salah (International Journal Of Community Medicine And Public Health, 2024)
The postpartum period is a crucial phase for mothers, requiring close monitoring and care to address physical, emotional, and psychological challenges. Comprehensive support is provided to new mothers through postpartum homecare programs, which prioritise the prevention and management of problems such gestational diabetes, hypertension, and postpartum depression. These programs ensure timely interventions for conditions like infections, excessive bleeding, and mental health concerns, which are common during this time. Homecare visits provide personalized care, with healthcare professionals offering guidance on breastfeeding, infant care, and self-care practices. The program's emphasis on maternal well-being reduces hospital readmissions and ensures early detection of serious conditions like postpartum hemorrhage and hypertension, promoting quicker recovery. Moreover, postpartum homecare enhances emotional support, helping new mothers cope with stress, anxiety, and fatigue. By fostering a strong mother-infant bond and addressing the unique needs of each patient, these programs contribute to better long-term health outcomes for both mother and baby, empowering women to confidently navigate the postpartum journey.